2021
DOI: 10.36835/iqtishoduna.v10i1.729
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Islamic Financing Schemes on Risk and Financing Performance in Islamic Banks in Indonesia

Abstract: The purpose of this study is to prove the effect of the financing scheme on financing risk and financing performance in Islamic banks in Indonesia. This research applies a form of quantitative research with the type of explanatory research that aims to accept or reject hypotheses. The population in this study are Islamic banks in Indonesia. The data used in the study are secondary data in the form of financial ratios sourced from Islamic bank financial reports for 2015 to 2019. Data analysis techniques use par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…The findings of this study that PMF has no effect on profitability, contradict the research conducted by Kuswara et al, (2019) which found that the PSF scheme with mudharabah products had a negative effect on profitability. Research results from Roziq & Sukarno (2021) show that PSF and PMF actually have a negative effect on profitability, thus contradicting the findings of this study. What needs attention in the findings of this study is that PMF has no effect on profitability while PSF has a positive effect.…”
Section: Hypothesis Test Resultscontrasting
confidence: 99%
“…The findings of this study that PMF has no effect on profitability, contradict the research conducted by Kuswara et al, (2019) which found that the PSF scheme with mudharabah products had a negative effect on profitability. Research results from Roziq & Sukarno (2021) show that PSF and PMF actually have a negative effect on profitability, thus contradicting the findings of this study. What needs attention in the findings of this study is that PMF has no effect on profitability while PSF has a positive effect.…”
Section: Hypothesis Test Resultscontrasting
confidence: 99%
“…The fact of this problem is not in line with the potential of fisheries households as measured by the fishermen exchange rate as an indicator of fishermen's welfare of 113.5 and the national fishermen exchange rate of 111.40 is still below the rate of Belitung (BPS, 2023). This means that the potential Fisheries Households in Belitung show promising potential and prospects for this sector (Roziq & Sukarno, 2021;Ilyas& Iskandar, 2023). The current Islamic financing schemes related to these problems can use Mudarabah and Musharakah contracts with a profit-sharing scheme (Arshed, et.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2021;Asiyah, et. al., 2021;Roziq & Sukarno, 2021). By this financing scheme, Islamic Commercial Banks get income from profit sharing, margin and rental income (Sudarsono & Saputri, 2018;Maulana & Rusmita, 2019;Yustiardhi, et.…”
Section: Introductionmentioning
confidence: 99%